2020
DOI: 10.4049/jimmunol.2000584
|View full text |Cite
|
Sign up to set email alerts
|

PIK3IP1 Promotes Extrafollicular Class Switching in T-Dependent Immune Responses

Abstract: PI3K plays multiple roles throughout the life of a B cell. As such, its signaling is tightly regulated. The importance of this is illustrated by the fact that both loss-and gain-of-function mutations in PI3K can cause immunodeficiency in humans. PIK3IP1, also known as TrIP, is a transmembrane protein that has been shown to inhibit PI3K in T cells. Results from the ImmGen Consortium indicate that PIK3IP1 expression fluctuates throughout B cell development in a manner inversely correlated with PI3K activity; how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 85 publications
0
4
0
Order By: Relevance
“…However, strong PI3K signaling also inhibits CSR (59,60). In T-dependent EF responses, antagonism of the PI3K signaling pathway via activity of PI3K interacting protein 1 (PIK3IP1) promotes CSR, which was recently demonstrated by Ottens and colleagues (61). Mice with CD19-cre mediated PIK3IP1 deletion show delayed production of IgG1 after immunization with NP conjugated to keyhole limpet hemocyanin (KLH), a T-dependent antigen.…”
Section: Extrafollicular B Cell Developmentmentioning
confidence: 97%
“…However, strong PI3K signaling also inhibits CSR (59,60). In T-dependent EF responses, antagonism of the PI3K signaling pathway via activity of PI3K interacting protein 1 (PIK3IP1) promotes CSR, which was recently demonstrated by Ottens and colleagues (61). Mice with CD19-cre mediated PIK3IP1 deletion show delayed production of IgG1 after immunization with NP conjugated to keyhole limpet hemocyanin (KLH), a T-dependent antigen.…”
Section: Extrafollicular B Cell Developmentmentioning
confidence: 97%
“…In human activated PI3K-δ syndrome (APDS), caused by mutations in PIK3CD and PIK3R1, hyperactive mTOR is linked to defective class-switch recombination (CSR) and conventional memory formation and enhanced formation of EF (CD21 low T-bet + ) B cells and ASCs (17,82,83). Defective CSR was also observed in mouse models with conditional deletion of the PI3K inhibitor PIK3IP1 (84). We showed that in FAS-competent B cells, FAS engagement can modulate mTOR activation in vitro, and this modulation was abrogated in ALPS-FAS patients' B cells.…”
Section: Discussionmentioning
confidence: 99%
“…[16]. 1:1000, 1:4000, and 1:16 000 dilutions of serum and 1:10, 1:40, and 1:160 dilutions of culture supernatant were subjected to total IgM, IgG, IgG1, and IgG2c ELISA as described [16,47].…”
Section: Elisasmentioning
confidence: 99%